2021
DOI: 10.3389/fendo.2021.627395
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Circulating Growth Differentiation Factor 15 Levels and Diabetic Retinopathy in Patients With Type 2 Diabetes

Abstract: ObjectiveGrowth differentiation factor 15 (GDF-15) is a member of the TGF-β superfamily that has anti-inflammatory properties. The objective of this study was to evaluate the relationship between circulating GDF-15 levels and diabetic retinopathy (DR) in patients with type 2 diabetes.Materials/MethodsA case–control study was performed in which 402 patients with type 2 diabetes were enrolled. Of these, 171 patients had DR and the remaining 231 patients without DR acted as controls. The plasma GDF-15 levels were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…Regarding diabetic complications, several reports have demonstrated the role of serum GDF15 in diabetic nephropathy and have suggested that GDF15 is a predictor of diabetic kidney disease [ 38 , 39 , 40 , 41 , 42 ]. Furthermore, recent studies have described the association between serum GDF15 and diabetic retinopathy both in T2DM [ 22 , 23 ] and T1DM [ 39 ], reporting that the plasma GDF15 level is a significant predictor of diabetic retinopathy, while there is a trend between increased plasma GDF15 level and severity of retinopathy in T2DM. While this study did not investigate diabetic retinopathy in particular, we indeed demonstrate that circulating GDF15 is elevated in subjects with diabetic nephropathy and is positively correlated with urine ACR and negatively correlated with eGFR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding diabetic complications, several reports have demonstrated the role of serum GDF15 in diabetic nephropathy and have suggested that GDF15 is a predictor of diabetic kidney disease [ 38 , 39 , 40 , 41 , 42 ]. Furthermore, recent studies have described the association between serum GDF15 and diabetic retinopathy both in T2DM [ 22 , 23 ] and T1DM [ 39 ], reporting that the plasma GDF15 level is a significant predictor of diabetic retinopathy, while there is a trend between increased plasma GDF15 level and severity of retinopathy in T2DM. While this study did not investigate diabetic retinopathy in particular, we indeed demonstrate that circulating GDF15 is elevated in subjects with diabetic nephropathy and is positively correlated with urine ACR and negatively correlated with eGFR.…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of GDF15 has been noted to protect against high-fat diet-induced obesity and glucose intolerance [ 17 ], while GDF15-knockout mice have been reported to gain body weight and store fat, concomitant with increased food intake [ 18 ]. As to diabetic complications, previous studies have demonstrated that serum GDF15 concentrations are related to cardiovascular disease and diabetic nephropathy and retinopathy [ 19 , 20 , 21 , 22 , 23 ], indicating its potential role as a novel biomarker.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to TGF-β isoforms and BMPs, many other TGF-β family members may also be involved in DR. One such member is growth differentiating factor 15 (GDF-15), whose precise intracellular mechanisms are not yet known [ 61 ]. GDF-15 expression increases in ischemic states and has been shown to be associated with cardiovascular injury and inflammation, including retinal vascular pathologies such as DR [ 61 , 62 ]. In fact, previous studies have demonstrated that serum concentrations of GDF-15 can be positively correlated with DR and may hold value as biomarkers for identifying the disease [ 62 ].…”
Section: Other Association Of Tgf-β Superfamily Signaling Pathway In Drmentioning
confidence: 99%
“…An in vitro study with human umbilical vein endothelial cells (HUVECs) showed that GDF-15 blocked angiogenesis by blocking endothelial tube formation by connective tissue growth factor 2 (CCN-2), a protein known for its proangiogenic functions [ 63 ]. GDF-15 has shown anti-inflammatory qualities by inhibiting the ability of leukocytes to interact with integrin or arrest along the vascular endothelium and by modulating pathways involved in oxidative stress [ 61 , 62 ]. This may be another mechanism by which GDF-15 plays a role in the pathogenesis of DR.…”
Section: Other Association Of Tgf-β Superfamily Signaling Pathway In Drmentioning
confidence: 99%
“…These levels increase with age, pregnancy, exercise, smoking and obesity, and are also influenced by genetic and environmental factors ( 29 , 40 ). GDF15 is highly expressed in vascular smooth muscle cells, cardiomyocytes, endothelial cells, macrophages and adipocytes during oxidative stress, inflammation, tissue damage and cancer ( 41 , 42 ). GDF15 is elevated in a variety of cancers, including those of the prostate, colon, pancreas and breast ( 31 , 39 ).…”
Section: Characteristics Of Gdf15mentioning
confidence: 99%